PREDIKSI KEBANGKRUTAN PADA PERUSAHAAN FOOD & BEVERAGE MODEL ALTMAN Z-SCORE, SPRINGATE DAN ZMIJEWSKI (Studi Kasus Pada PT. FKS Food Sejahtera Tbk Tahun 2020-2022) - Erliana, Lia; Solikah, Mar’atus; Astuti, Puji (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to analyze the prediction of potential bankruptcy at PT. FKS Food Sejahtera Tbk, a company in the food and beverage sector which is listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. The analysis was carried out using three prediction models, namely Altman Z-Score, Springate, and Zmijewski. The research method used is descriptive with a quantitative approach. The results of the study show that the three prediction models provide different results regarding the potential for corporate bankruptcy. Based on the Altman Z-Score and Springate models, the company is predicted to be unhealthy or has the potential to experience bankruptcy. However, based on Zmijewski's model, the company is categorized as a healthy company. The main difference between this research and previous studies is the place and time of research, as well as the data studied. This shows that the bankruptcy prediction results may vary depending on the model used and the condition of the company in a certain period.